2011
DOI: 10.1007/978-3-642-20862-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Gossip-Based Networking for Internet-Scale Distributed Systems

Abstract: Abstract. In the era of Internet-scale applications, an increasing number of services are distributed over pools of thousands to millions of networked computers. Along with the obvious advantages in performance and capacity, such a massive scale comes also with challenges. Continuous changes in the system become the norm rather than the exception, either because of inevitable hardware failures or merely due to standard maintenance and upgrading procedures. Rather than trying to impose rigid control on the mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Gossip protocols are often employed in such situations, ranging from straightforward uniform techniques [37] to more sophisticated stratification of gossip targets and probabilities [38], [39]. By building on top of these or other types of scalable communication mechanisms, reputation-based trust can be used to protect key assets, including cyberphysical critical infrastructure protection systems [40]. This same genre of technique can also be applied to the types of social media networks discussed in this article.…”
Section: Gossip Protocols On Distributed Systemsmentioning
confidence: 96%
“…Gossip protocols are often employed in such situations, ranging from straightforward uniform techniques [37] to more sophisticated stratification of gossip targets and probabilities [38], [39]. By building on top of these or other types of scalable communication mechanisms, reputation-based trust can be used to protect key assets, including cyberphysical critical infrastructure protection systems [40]. This same genre of technique can also be applied to the types of social media networks discussed in this article.…”
Section: Gossip Protocols On Distributed Systemsmentioning
confidence: 96%
“…Moreover, many users may share enough resources to compute very complex queries which are currently out of their individual scope. Recent research has demonstrated the effectiveness of epidemic protocols in a variety of settings [24], [25], [26]. These include not only traditional peer-to-peer applications such as data dissemination or overlay maintenance, but also user-oriented tasks such as identifying communities with similar interests, or recommendation systems.…”
Section: A Query and Indexationmentioning
confidence: 99%
“…In particular, we designed DATAFLASKS based on a stack of gossip or epidemic protocols which are known for their scalability and resilience under highly dynamic environments. They have been successfully used to build several webscale systems and applications [9] like overlay construction and maintenance [10], [11], consensus [12], data aggregation [13], distributed slicing [14]- [17] and live video streaming [18]. One key characteristic of these protocols is that they rely solely on partial data about the system.…”
Section: Introductionmentioning
confidence: 99%